The BAWSO Diogel Project. A conversation with Imogen Gunner, BAWSO Trafficking Senior Support Worker - Jackie Jones (Oñati Socio-Legal Series)
This contribution to the special issue is a contextual interview providing an insight into the work of a senior support worker of victims of trafficking in Wales; victims who often apply for asylum at the same time as trying to recover from extreme exploitation and vulnerabilities. Some of the relevant legal provisions in England and Wales will be outlined, particularly in relation to the Modern Slavery Act 2015, to provide the reader with some key constraints both the victim and worker must adhere to stay within the law. The contextual interview also provides a picture of Albanian and Nigerian victims of trafficking and their treatment in the UK as well as a case study presented to politicians, representing a victim’s life before arriving in the UK, demonstrating her extreme vulnerabilities in her home country of Nigeria. Finally, some common threads and conclusions will be drawn out.